Terms of trade movements and the global economic crisis - Bloch, Harry; Sapsford, D. (Routledge, 2011)
Dramatic changes in the relative prices of goods in international trade haveaccompanied, and indeed preceded, the recent global crisis. The causes and effectsof the relative price changes are analysed by applying the analysis of businesscycles developed by Joseph Schumpeter. Schumpeter’s analysis emphasisesinnovation and structural change (particularly creative destruction) which impartuneven development on the economy and can foster financial crises. This puts thecurrent crisis in the context of long-wave development of the capitalist system andleads to predictions about the likely path of price and output changes over the nextfew decades.